THE INTRODUCTION OF E-GOVERNMENT IN THE REPUBLIC OF NORTH OSSETIA-ALANIA (LEGAL ASPECT) - Z. T. Zoloeva; B. G. Koybaev (Гуманитарные и юридические исследования, 2021)
The article analyzes the Federal and regional legislation, as well as conceptual documents regulating the functioning of e-government in the Russian Federation regions. The study attempts to identify the existing problems and ways to tune the legislation of the Republic of North Ossetia - Alania in the field under consideration.